Analisis Laba Usaha Dengan Menggunakan Metode Economic Value Added ( EVA ) Pada Koperasi Karyawan Tirta Mahakam di Tenggarong - Hermanto, Muhammad (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
The good realization cooperation must be supported with professional financial management system. Tirta Mahakam Employee Cooperation is a cooperation which is built by PDAM Kutai Kartanegara, its destination is to increase the employee’s prosperity. This cooperation’s labor activity is shop matters which provide the need of nine basic material, where’s this cooperation shop besides serve the members’ need also serve the citizens.One of methods which is used to analyze the capability of company’s finance is EVA method (Economic Value Added). On counting EVA (Economic Value Added) by decrease the operation profit after tax with financial capital total. Key Word : Cooperation, Capability